Vpliv omejitev gibanja za obvladovanje širjenja virusa SARS-CoV-2 na 24-urno gibalno vedenje in telesno zmogljivost otrok in mladostnikov - Ocvirk, Tjaša (Šport (Ljubljana), 2021)
COVID-19 disease epidemic has drastically changed the lifestyle of children and adolescents as schools closed, extracurricular activities ceased, and social distancing became the new normal. The article presents a review of literature of movement restriction on physical activity, sedentary behaviour and sleep of children and adolescents. Literature search was performed in three online databases (UNICEF, PubMed and Google Scholar) and 34 studies were included in the analysis. During the epidemic children and adolescents were less physically active, they especially decreased moderateto high-intensity physical activity, due to the movement restrictions and limited opportunities for structured exercise within sport clubs. As a result, they were more sedentary and increased their screen time. Furthermore, students prolonged their total sleep time since changed school schedule allowed them to wake up later in the morning and go to bed later in the evening. Overall, children and adolescents were less compliant with the Canadian 24-hour movement behaviour recommendations, which can negatively affect their physical fitness and health outcomes. Changes in children's and adolescent's movement behaviour require immediate action, as they can maintain new habits even in adulthood, which can have a negative impact on their quality of life.
Keywords: adolescents; children; COVID-19; epidemic; epidemije; gibalno vedenje; mladostniki; movement behaviour; otroci; physical activity; physical fitness; sleep; spanje; sport; šport; telesna dejavnost; telesna zmogljivost; youth